1999
DOI: 10.1557/s1092578300002593
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surface Preparation on Epitaxial GaN on 6H-SiC Deposited Via MOCVD

Abstract: A comparison was made of 6H-SiC surfaces etched with H 2 , C 2 H 4 /H 2 , and HCl/H 2 , and the resulting crystal quality of epitaxial GaN films deposited on these substrates. To remove the many fine scratches and to smooth the rough surfaces typical of commercial SiC substrates, the Si-face 6H-SiC substrates were etched in H 2 , C 2 H 4 /H 2 , and HCl/H 2 at 1450 o C. GaN was subsequently deposited on these etched surfaces after first depositing a low temperature GaN buffer layer via metalorganic chemical vap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Difficulties in preparing the surface of the SiC substrates prior to growth [1][2][3][4][5] have largely been overcome and HEMT structures with electrical performance characteristics comparable to or better than those grown on sapphire substrates have been obtained. In this paper we report the use of ammonia-MBE for the growth of AlGaN/GaN two dimensional electron gas (2DEG) structures on insulating 4H-SiC (0001) substrates using a magnetron sputter epitaxy (MSE) deposited AlN buffer layer and carbon doped channel isolation layers [6].…”
Section: Introductionmentioning
confidence: 99%
“…Difficulties in preparing the surface of the SiC substrates prior to growth [1][2][3][4][5] have largely been overcome and HEMT structures with electrical performance characteristics comparable to or better than those grown on sapphire substrates have been obtained. In this paper we report the use of ammonia-MBE for the growth of AlGaN/GaN two dimensional electron gas (2DEG) structures on insulating 4H-SiC (0001) substrates using a magnetron sputter epitaxy (MSE) deposited AlN buffer layer and carbon doped channel isolation layers [6].…”
Section: Introductionmentioning
confidence: 99%
“…This partial coalescence can be due to the use of a relatively low growth temperature. This consideration has been made by other authors (Xie et al, 1999) who found that in GaN films grown by MOCVD, the density of random pinholes decreases by increasing the growth temperature.…”
Section: Sem Measurementsmentioning
confidence: 75%
“…Most gallium nitride based epitaxial structures are grown on sapphire but for power devices silicon carbide with its high thermal conductivity is more suitable for high-power applications. SiC substrates as-received from a supplier have a scratch-covered surface but a meaningful improvement of the substrate surface quality is provided by wafer polishing laboratories or by means of an in -situ substrate preparation process [1]. Thus, the surface preparation is required and it has a big impact on device performance because it can primarily improve the crystallographic structure of epilayer.…”
Section: Introductionmentioning
confidence: 99%